Estimation and compensation of nonideal front-end effects for MB-OFDM based ultra wideband system - LIU Liang; ZHOU Jun; YE Fan; REN Jun-yan (Tongxin xuebao)
Three types of wireless system frontend imperfections, namely carrier frequency offset （CFO）, sampling frequency offset （SFO） and in-phase/quadrature-phase （I/Q） imbalance were addressed. A time-domain CFO and I/Q imbalance estimation and compensation scheme for MB-OFDM based ultra-wideband （UWB） system was proposed. In the scheme, a data-aided CFO estimation algorithm, which was robust to large I/Q imbalance, was presented. Also, a time-domain I/Q imbalance estimation algorithm was introduced. Finally a two-step joint CFO and I/Q imbalance compensation scheme was developed. In frequency domain, a residual CFO and SFO estimation algorithm using the time-domain spreading feature of the UWB frame header was presented. The proposed scheme is competent for large front-end imperfections, and the results are confirmed by simulations.